Purification and characterization of catechin from cascara and its evaluation on antioxidant and antibacterial activities - Sholichah, Enny; Desnilasari, Dewi; Karim, Mirwan Ardiansyah; Putra, Aditya; Purwono, Bambang (AIP Conference Proceedings, 2022)
Cascara is an infusion beverage produced by coffee bean production. Research on isolation and characterization of catechin, antioxidant activity test and antibacterial test of cascara has been conducted. Isolation of catechin from cascara arabica and robusta was done by maceration with ethanol 95% for 24 hours and column chromatography with acetone-water (1:1) as mobile phase and silica gel as the stationary phase. The isolates were characterized by Thin Layer Chromatography (TLC), UV-Visible and FTIR spectrophotometers. The antioxidant activity of each isolate was measured by DPPH (2,2-diphenyl-1-picrylhydrazyl) method and the antibacterial activity was tested by a disk diffusion method. The UV-Visible and FTIR spectra of the two isolates showed similar spectra with the catechin standard. The radical scavenging activity (RSA) of catechin isolates from cascara arabica and robusta were 78% and 76%, respectively. The antibacterial activity measurement showed that both isolates had relatively moderate-strong antibacterial activity against E.coli and S.aureus. The yield of isolated catechin of arabica, and robusta cascara were 0.02% and 0.01% sequentially